2022
DOI: 10.31616/asj.2021.0371
|View full text |Cite
|
Sign up to set email alerts
|

An Updated Overview of Low Back Pain Management

Abstract: We aimed to determine the recommendation level for the treatment of acute and chronic low back pain (LBP). A systematic review (SR) of the literature was performed and all English-language articles that discuss acute and chronic LBP, including MEDLINE and the Cochrane Database of Systematic Reviews, were searched. Of the 873 searched literature reports, 259 articles, including 131 clinical trials, 115 SRs, nine meta-analyses, and four clinical guidelines were analyzed. In these articles, high-quality randomize… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
12
0
1

Year Published

2022
2022
2025
2025

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 138 publications
0
12
0
1
Order By: Relevance
“…LBP affects people of all ages and socioeconomic classes worldwide [4][5][6]. Previous studies have documented that 50% to 80% of people will experience LBP at least once in their lives, with a point prevalence of 15% to 30% and annual incidence of 15% to 45% [7][8][9]. Although LBP can develop in all age groups, it is most common in the working population, i.e., adults aged 35 to 55 years [2,5], with the overall prevalence and severity of LBP tending to increase over time [10,11].…”
Section: Epidemiology and Natural Historymentioning
confidence: 99%
“…LBP affects people of all ages and socioeconomic classes worldwide [4][5][6]. Previous studies have documented that 50% to 80% of people will experience LBP at least once in their lives, with a point prevalence of 15% to 30% and annual incidence of 15% to 45% [7][8][9]. Although LBP can develop in all age groups, it is most common in the working population, i.e., adults aged 35 to 55 years [2,5], with the overall prevalence and severity of LBP tending to increase over time [10,11].…”
Section: Epidemiology and Natural Historymentioning
confidence: 99%
“…After receiving appropriate conservative treatment for at least 2-3 months, surgery is recommended when patients complain of pain, muscle weakness, and gait disturbance caused by lower-extremity paresthesia, which affect their daily life. Surgery is rarely used to treat low back pain caused by spondylolisthesis and scoliosis when there is no instability [48]. It is difficult to predict the likelihood of recovery after surgery, even when uncommon long-term motor paralysis is the main symptom; thus, other causes should be identified prior to surgery.…”
Section: Principles Of Spinal Stenosis Surgerymentioning
confidence: 99%
“…Patients with LBP may recover spontaneously, but some LBP patients will develop chronic LBP (CLBP) [ 5 ]. From the third decade of life until age 60, the prevalence increases linearly, with a greater frequency among women [ 2 , 6 ]. In addition, a recent meta-analysis revealed that 21–68% of patients aged 60 or older had LBP in the preceding year, indicating the significant prevalence of CLBP among older persons [ 7 ].…”
Section: Introductionmentioning
confidence: 99%